Design of a rotary roaster for cassia sieberiana seeds (2004)
Two kilogram capacity roaster was designed and fabricated for purpose of roasting cassia sieberiana seeds obtained from an African plant, which is capable of being used as coffee substitute. During the testing of the roaster, physical changes on the seeds were monitored and found to be temperature and time dependent. Best samples of roasted cassia sieberiana was obtained at 200⁰C roasting temperature after 15minutes.